Time-lapse imaging of identified granule cells in the mouse dentate gyrus after entorhinal lesion in vitro reveals heterogeneous cellular responses to denervation - Greco, Davide; Drakew, Alexander; Rößler, Nina; Jungenitz, Tassilo; Jedlicka, Peter; Deller, Thomas (Frontiers in Neuroanatomy, 2025)
Denervation of neurons is a network consequence of brain injury. The effects of denervation on neurons can be readily studied in vitro using organotypic slice cultures of entorhinal cortex and hippocampus. Following transection of the entorhino-dentate projection, granule cells (GCs) are denervated and show on average a transient loss of spines on their denervated distal dendrites but not on their non-denervated proximal dendrites. In the present study, we addressed the question how single GCs and their denervated and non-denervated segments react to entorhinal denervation. Local adeno-associated virus (AAV)-injections were employed to transduce dentate GCs with tdTomato and entorhinal projection neurons with EGFP. This made it possible to visualize both innervating entorhinal fibers and their target neurons and to identify dendritic segments located in the “entorhinal” and the “hippocampal” zone of the dentate gyrus. Confocal time-lapse imaging was used to image distal and proximal segments of single GCs after entorhinal denervation. Time-matched non-denervated cultures served as controls. In line with previous reports, average dendritic spine loss was 30% (2–4 days post-lesion) in the denervated zone. However, individual GCs showed considerable variability in their response to denervation in both layers, and both decreases as well as increases in spine density were observed at the single cell level. Based on the standard deviations and the effect sizes observed in this study, a computer simulation yielded recommendations for the minimum number of neurons that should be analyzed in future studies using the entorhinal in vitro denervation model.